Prediction of librarian interest in library management in Pamekasan with comparison of SVM and KNN algorithms - Lathifah, Lathifah; Yuadi, Imam (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2025)
This study was conducted to determine the prediction of librarian interest in joining a library organization. Using survey data and interviews with librarians that produced 130 test data then divided into two groups of data, namely